THE EFFECTS OF SHORT STORY THROUGH WATTPAD ON READING COMPREHENSION ACHIEVEMENT OF NON- ENGLISH MAJOR STUDENTS OF BINA DARMA UNIVERSITY - Dewi Purnama Sari (Politeknik Negeri Sriwijaya, 2016)
Integrating technology and literature in English language teaching has been quite useful nowadays, especially for undergraduate students. One of the technologies which promotes literature is Wattpad. The use of Wattpad in this research was to gain students’ attention to read more, find the stories they were interested in, and apply their ability to think critically by giving comments or express their feelings. The study aimed at investigating the reading comprehension achievement of the students after being taught by using short story through Wattpad. The 60 non-English students of Bina Darma University were selected. The results suggested the short story through Wattpad significantly affected the students’ reading comprehension achievement.